Efeitos da Lei Maria da Penha na Região Sudeste - Oliveira, Amanda Torres de (Universidade Federal de São Carlos, 2020)
In Brazil, records of domestic violence and femicide are considered very high and represent one of the most expressive forms of violence in the country. It is of interest to investigate the behavior of these registered numbers, because with the information collected and from the analysis it can become a possible starting point to motivate new interventions, these being through public policies that seek to change the scenario current in relation to femicide and violence in the domestic environment. One of these interventions occurred with the creation of the Maria da Penha law in 2006, for the study in question, the objective is to describe and apply time series and regression techniques. with structural change to analyze the changes caused by the law in the Southeast region of Brazil.
Effects of the Maria da Penha Law in the Southeast Region
Keywords: Feminicídio; Lei Maria da Penha; Regressão; Séries temporais; Troca Estrutural; Violência Doméstica; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA::ESTATISTICA::REGRESSAO E CORRELACAO